Pengembangan Media Sosial sebagai Sistem Informasi di MI Muhammadiyah Taraman, Sragen - Yudi Wahyu W; Cahyaningtyas S W; Dedi Gunawan; Arif Surya Kusuma (Yayasan Literasi Sains Indonesia, 2026)
Madrasah Ibtidaiyah Muhammadiyah (MIM) Taraman in Sragen Regency has faced challenges regarding a decline in new student enrollment due to suboptimal digital promotion strategies. Despite utilizing social media platforms, the lack of strategic management has failed to effectively attract prospective parents. This community service program aims to enhance the school's visibility through the development of a modern and interactive school information system. The implementation method employed three primary strategies: lectures, discussions, and practical simulations. The implemented solutions included the development of a school profile website integrated with AI Chatbot technology for 24/7 information services and an analytics dashboard to monitor publication effectiveness. Beyond technical aspects, the program focused on human resource capacity building through training in content management, digital branding, and technical assistance for teachers and staff. The results indicate a significant impact on the partners' digital literacy. Based on post-test data, all participants (19 individuals) expressed a clear understanding and agreement regarding the utilization of information systems and social media as effective promotional tools. The implementation of this technology is expected to expand MIM Taraman's promotional reach and increase student enrollment in the upcoming academic year.